Chronic Granulomatous Disease - Shreya Agarwal (Journal of Clinical and Diagnostic Research, 2015)
Chronic Granulomatous Disease (CGD) is an inherited immunodeficiency disorder characterized by defective functioning of NADPH oxidase enzyme in the phagocytes. This leads to recurrent infections by catalase positive organisms and later, granuloma formation in multiple organs. This condition usually presents in the age group of 2-5 y and is uncommon in neonates. In this case report, we describe a rare case of CGD in a 40-day-old male child who initially presented with a history of erythematous pustular rash on left forearm and refusal to feeds. He remained unresponsive to regular antibiotics. CT chest and abdomen revealed multiple ill-defined lesions suggestive of granulomas or developing abscesses. Immunodeficiency workup showed negative Nitroblue Tetrazolium test and positive Dihydrorhodamine test (flow cytometry). A diagnosis of CGD was then made and treated accordingly. The aim of this report is to highlight the fact that although it is rare for CGD to present at such an early age, but in a neonate with multiple granulomas or abscesses, it should be considered as a differential and worked up accordingly. Early diagnosis and treatment can significantly improve the prognosis.